MORPHOLOGICAL PROPERTIES MESENTERIAL GLAND OF FETUS AND NEWBORNS FROM HIV-INFECTED - Sorokina, I.V.; Sherstiuk, S.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
With the purpose of determination morphological properties mesenterial gland of fetus and newborns from  HIV-infected, lymphoid component of organ was investigated with using morphological and morphometric methods. Was found morphological signs significant changes functional activity of T-lymphocytes and in less degree depression population of of B-lymphocytes.